PENGEMBANGAN ALAT UKUR EVALUASI DAN PERANCANGAN PRODUK KURSI RODA - Hapsoro Agung Jatmiko; Rini Dharmastiti (Universitas Gadjah Mada, 2018)
A wheelchair is one of the mobility aids for people with disabilities. Availability of wheelchair type is very decisive for users based on the limitations they have. The problem felt by users in Indonesia today, especially in Yogyakarta, is that users have not got the right kind of wheelchairs with the needs, with certain limitations. This study aims to develop a wheelchair evaluation and to know the user's expectation of the wheelchair design. This study shows that there are problems due to the users not getting a wheelchair that suits their needs. The wheelchair design that the users want are the wheelchair with 3 wheels and have new feature.